Pengaruh Electronic Word Of Mouth Dan Citra Merek Terhadap Keputusan Pembelian Aplikasi Tokopedia - Wala Erpurini; Nur Alamsyah; Eli Nofita Sari (TEMATIK, 2024)
This study evaluates the influence of Electronic Word of Mouth (eWOM) and brand image on the purchasing decisions of students of the Faculty of Economics, Pasim Bandung National University on the Tokopedia application. eWOM includes reviews, testimonials, and recommendations through digital platforms, while brand image refers to students' perceptions of Tokopedia as a brand. This study uses a survey method with a questionnaire to collect data from students who have used the Tokopedia application. The analysis was conducted with multiple linear regression to determine the relationship between eWOM, brand image, and purchasing decisions. The results showed that eWOM had an influence of 4.7% on purchasing decisions, while brand image had an influence of 59.8%. Hypothesis testing shows that eWOM and brand image significantly influence purchasing decisions, with an R2 value of 0.646. Thus, about 64.6% of the variation in purchasing decisions on the Tokopedia application can be explained by the combined influence of eWOM and brand image. The remaining 35.4% is caused by other factors not examined in this study.